Emotionally intelligent school leadership predicts educator well-being before and during a crisis - Floman, James L.; Ponnock, Annette; Jain, Jahnvi; Brackett, Marc A. (Frontiers in Psychology, 2024)
We examined the role of educator perceptions of school leader emotion regulation (ER) and emotional support (ES) in educator well-being during a typical year and during the COVID-19 pandemic. Based on emotion contagion theory, leaders' (in)ability to regulate their own emotions may trigger ripple effects of positive or negative emotions throughout their organizations, impacting staff well-being. Additionally, based on conservation of resources theory, when experiencing psychologically taxing events, skillful emotional support provided by leaders may help to replenish staff's depleted psychological resources, promoting staff wellbeing. In two national studies, a cross-sectional (NStudy 1 = 4847) and a two-wave study (NStudy 2 = 2749), we tested the association between U.S. preK-12 educator perceptions of school leaders' ER and ES with educator well-being before and during the COVID-19 pandemic, employing structural equation modeling and multilevel modeling. In Studies 1 and 2, educator reports of their leaders' ER and ES skills predicted greater educator well-being (e.g., positive affect and job satisfaction) and less educator ill-being (e.g., emotional exhaustion and turnover intentions) as indicated by subjective reports. In moderation analyses, perceived leader ER predicted wellbeing about equally among educators facing severe versus mild health impacts from COVID-19. In contrast, perceived leader ES was more strongly associated with educator well-being in those severely versus mildly impacted by COVID-19 illness and death. Leader ER played a role in the well-being of everyone, whereas leader ES was more predictive of well-being for those severely impacted by a crisis. Regarding implications for policy and practice, efforts to promote wellbeing among educators may be enhanced when combined with efforts to develop school leader ER and ES skills, especially in times of crisis. Accordingly, school districts should consider the value of investing in routine, evidence-based emotion skills training for their school leaders.